Pengaruh Budaya Organisasi dan Gaya Kepemimpinan terhadap Kinerja Pegawai DPMDPPKB Kabupaten Pesisir Selatan - Zusmawati Zusmawati; Sonny Hakri (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
The availability of quality human resources provides an opportunity for leaders to select the best employees for strategy implementation. However, the effectiveness of strategy implementation depends not only on human resources but also on the organizational culture and leadership style applied. Based on the results of the first hypothesis test, it was found that the organizational culture variable has a positive and significant effect on employee performance at the Pesisir Selatan Regency DPMDPPKB. Therefore, in this study, the first hypothesis (H1) is accepted. Based on the results of the second hypothesis test, it was found that the leadership style variable has a positive and significant effect on employee performance at the Pesisir Selatan Regency DPMDPPKB. Therefore, in this study, the second hypothesis (H2) is accepted. Organizational culture partially has a positive and significant effect on employee performance. Therefore, it can be concluded that if organizational culture improves, employee performance will also improve. Leadership style has a positive and significant effect on employee performance. Therefore, it can be concluded that if leadership style improves, employee performance will also improve. Organizational Culture and Leadership Style simultaneously have a positive and significant effect on employee performance at the Pesisir Selatan Regency DPMDPPKB. Therefore, it can be concluded that if Organizational Culture and Leadership Style improve simultaneously, employee performance will also improve.